Corporate Governance and Ethical Leadership: The Pillars of Effective Business Management - Ali Mabruk Masadak (المجلة الأفروآسيوية للبحث العلمي, 2024)
This research highlights the important nexus between corporate governance and ethical leadership, clarifying their key roles as fundamental pillars of effective business management. The main objectives of the study are to understand the interaction between corporate governance and ethical leadership, analyze their impact on business management, and provide practical insights to promote a sustainable and ethical corporate environment. Methodologically, a comprehensive literature review was conducted, which included models of corporate governance, ethical leadership theories, and basic work on their confluence. Additionally, some case studies were investigated to find concrete examples of successful integration of these principles. Quantitative and qualitative data were analyzed, providing an important understanding of the subject. The results indicate an intrinsic link between transparent and accountable corporate governance structures and the cultivation of ethical leadership. Studies show that businesses that adopt stakeholder engagement strategies experience better business management outcomes. Furthermore, a robust risk management framework has been identified as integral to both corporate governance and ethical leadership, reducing potential drawbacks and promoting sustainable business practices. Corporate culture emerges as a lynchpin, with ethical leadership playing an important role in shaping values and practices that resonate throughout the organization.